1995
DOI: 10.1021/j100013a046
|View full text |Cite
|
Sign up to set email alerts
|

Salt Effect on Wetting/Nonwetting Behaviors

Abstract: We study the phase behavior, the wettinglnonwetting behaviors, and the wetting transition of systems of the type water + n-alkane + diethylene glycol monohexyl ether (C6E2) + salt. Three systems-water + n-tetradecane + C6E2 + NaC1, water + n-hexadecane + C6E2 + NaC1, and water -I-n-octadecane + C6E2 + NaC1-are used to demonstrate that the effect of adding a lyotropic salt (NaC1) on phase and interfacial behaviors is equivalent to that of raising the temperature. For all three systems, there exists a middle / 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…[9] and [10] simultaneously and therefore is purely algebraic, and the other is to introduce undetermined multipliers (25). We employ the latter because it has been reported that it offers distinct physical meanings to the undetermined multipliers (25 [11] where the superscript indicates that a quantity with is the surface excess one introduced in Eq.…”
Section: Thermodynamic Equations As a Function Of Temperature Pressumentioning
confidence: 99%
See 1 more Smart Citation
“…[9] and [10] simultaneously and therefore is purely algebraic, and the other is to introduce undetermined multipliers (25). We employ the latter because it has been reported that it offers distinct physical meanings to the undetermined multipliers (25 [11] where the superscript indicates that a quantity with is the surface excess one introduced in Eq.…”
Section: Thermodynamic Equations As a Function Of Temperature Pressumentioning
confidence: 99%
“…Wetting-nonwetting behavior is one of the interesting phenomena relevant to the properties and structures of interfaces (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). In our previous papers, the new apparatus and procedure for dihedral angle measurements have been shown to be very successful (11), and the state and phase transition of the interfacial films, the wetting behavior, the intruding phenomena, and the mutual relation among them have been discussed thoroughly with respect to the air/long-chain alcohol/water systems with a floating alcohol lens (12).…”
Section: Introductionmentioning
confidence: 99%
“…3 Such a transition had been experimentally observed in a vapor-liquid-liquid system of cyclohexane and methanol, 4 as well as in some other binary, [5][6][7] ternary, 8,9 and quaternary systems. 10 In addition, it was found that the wetting transition of a water + oil + amphiphile system in the three-liquid-phasecoexisting region occurs as the system is driven to either one of its critical end points by varying the temperature, [11][12][13][14][15][16] by varying the amphiphilicity, 11,17 by tuning the salinity, 18,19 and . Wetting behavior at a fluid-fluid interface: (a) a completewetting phase at the R-γ interface; (b) a partial-wetting phase at the R-γ interface; (c) a nonwetting phase at the R-γ interface; and (c*) a complete-wetting R phase at the γ-interface.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18] The symbol C i E j is the abbreviation of a nonionic polyoxyethylene alcohol C i H 2i+1 ͑OCH 2 CH 2 ͒ j OH. It was found that these ternary systems can exhibit diverse wetting behaviors by simply varying thermodynamic variables, such as temperature, [5][6][7][8][9][10][11][12] oil chain length, 13,15 amphiphilicity of an amphiphile, 6-10 and salinity.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that these ternary systems can exhibit diverse wetting behaviors by simply varying thermodynamic variables, such as temperature, [5][6][7][8][9][10][11][12] oil chain length, 13,15 amphiphilicity of an amphiphile, 6-10 and salinity. 17,18 The most intriguing phenomenon observed in the water + n-alkane ͑such as octane, decane, dodecane, or tetradecane͒ +C 6 E 2 system 12,13 was that the middle C 6 E 2 -rich phase would undergo a sequential wetting transition, nonwetting → partial wetting→ complete wetting, along with increasing temperature. This observation verifies the suggestion that the wetting behavior can be related to the temperature dependence of the amphiphilicity of a surfactant.…”
Section: Introductionmentioning
confidence: 99%